INTEGRATION PROCESSES IN CENTRAL ASIA AND PROSPECTS OF THE IDEA OF “TURKISTAN – OUR COMMON HOME " IN THIS REGION (Academicia Globe: Inderscience Research, 2021)
Central Asia is a region with its glorious history, ancient, great traditions and religious and secular culture. Studying the existing historical traditions in this region, continuing and enriching them in New historical conditions, inheriting a society that is comprehensively mature, perfect and sustainable for the future generation is today's urgent task. There are different views on cooperation between the countries of Central Asia and its prospects. But today, the countries of the region are solving the problems that will exist now and in the near future, establishing mutually beneficial and multilateral cooperation.